2021
DOI: 10.1159/000517403
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Accident and SARS-CoV-19 (COVID-19): A Systematic Review

Abstract: <b><i>Background:</i></b> While the most common neurologic symptoms reported in patients affected by SARS-CoV-2 are headache, dizziness, myalgia, mental fog, and anosmia, there is a growing basis of published peer-reviewed cases reporting stroke in the setting of SARS-CoV-2 infection. The peer-reviewed literature suggests an increased risk of cerebrovascular accident (CVA) in the setting of COVID-19 infection. <b><i>Methods:</i></b> We searched 3 databases (PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The median age of severe COVID patients was 63 years. The finding is consistent with other studies, including a systematic review that reported an average age of 60 years in hospitalized, 3 and a study involving 5700 hospitalized patients that reported a median age of 63. 4 However, it is worth noting that some studies have reported lower age estimates, such as 53.2 years for severe patients 5 and a median age of 52 years for severe cases.…”
Section: Discussionsupporting
confidence: 91%
“…The median age of severe COVID patients was 63 years. The finding is consistent with other studies, including a systematic review that reported an average age of 60 years in hospitalized, 3 and a study involving 5700 hospitalized patients that reported a median age of 63. 4 However, it is worth noting that some studies have reported lower age estimates, such as 53.2 years for severe patients 5 and a median age of 52 years for severe cases.…”
Section: Discussionsupporting
confidence: 91%
“…Stroke is a known neurological complication that substantially increases the disease severity and death risk in COVID-19 patients [87] and vice versa, patients with a more severe COVID-19 form are more predisposed to develop cerebrovascular diseases [71]. Although, in another systematic review, the authors state that there seems to be no association between COVID-19 severity and the risk of developing cerebrovascular disorders [6]. Apart from stroke, delirium was also linked to higher disease severity in COVID-19 patients as it leads to prolonged hospitalization, need for ICU admission, or in-hospital mortality [45,85].…”
Section: Neurological Manifestationsas Prognostic Factors In Covid-19mentioning
confidence: 98%
“…Pathophysiologically, COVID-19 infection has been associated with altered male reproduction, 81 olfactory dysfunctions, 82 abnormal liver function tests, 83 neurologic conditions, 84 cerebrovascular events, 85 hypovitaminosis D, 86 dysgeusia, 87 obesity, 88 and perturbations in energy homeostasis 89 just to mention a few. For instance, high-energy expenditure driven by a high metabolic state induced by the host response may quickly lead to depletion of the micronutrient.…”
Section: Alterations In Physiologic Responsesmentioning
confidence: 99%